3D animated visualization for traffic monitoring - Phan, Nguyen Thuy Duong. (2012)
This report, prepared for the Full-Time Final Year Project, will describe the design of the 3D Animated Visualization for Traffic Monitoring. The project consists of 3D animated visualization of a radar surveillance system initially developed by the researchers at the Centre for Signal Processing. The objective of the project is to extend the developed 3D visualization system for road traffic monitoring. The radar system is made up of a continuous-wave K-band (24.15 GHz) Doppler radar and produces tracks associated with the moving objects within the radar beam. These tracks could be used to determine the presence, speed and distance of any object illuminated by the radar. Using the track information, with animation software (e.g. Autodesk 3ds Max 9) to model and render 3D graphics for environments (roads, rain conditions) and objects (cars, vans, motor bikes etc.), a 3D traffic visualization can be achieved which provides a better Human-Machine Interface.